APAKAH VACA, VAHU, STVA MEMPENGARUHI PROFITABILITAS? STUDI PADA BANK BCA SYARIAH 2017-2022 - Dewi, Anggita Rosiana (Jurnal Akuntansi, 2023)
The purpose of this study is to investigate how BCA Syariah Bank's profitability is impacted by VACA, VAHU, and STVA. The study employed a quarterly financial report covering the period from 2017 to 2022 as its sample. Using a purposive sampling approach and a 6year observation period, 24 samples of observation data are acquired from the population, which is BCA Syariah Bank. The Financial Services Authority website published financial statements, which provided the data needed for this investigation. Multiple linear regression analysis is used in the data analysis process. by utilizing SPSS version 21 as a research instrument. The study's findings show that VACA significantly and favorably affects BCA Syariah Bank's profitability. VAHU significantly and negatively affects BCA Syariah Bank's profits. Furthermore, STVA has no impact on BCA Syariah Bank's profits.